ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL (Studi Empiris di Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020 - 2023) - Anastasya Nursiva Yuniar; Widi Hariyanti; Yunus Harjito (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to examine how profitability, asset structure, liquidity, company size, sales growth, and business risk affect capital structure. The object of this study is manufacturing companies listed on the Indonesia Stock Exchange in the period 2020-2023. The research sample consisted of 142 companies selected through a purposive sampling method, so that the total data used was 568, calculated from 142 companies multiplied by 4 years of research. After removing 37 outlier data, the amount of data analyzed was 531. The analysis techniques used included multiple linear regression and simple linear regression with the help of SPSS 21 software. The results of the study revealed that profitability, asset structure, liquidity, and business risk had a negative effect on capital structure. Meanwhile, company size and sales growth did not affect capital structure. Keywords : Capital Structure, Profitability, Liquidity, Firm Size, and Sales Growth